Islamic Educators Development Strategy in Improving Professional Competence Towards Sustainable Development Goals (SDGs) - Hidayatussaliki; Sugeng Listyo Prabowo; Slamet; Mappanyompa; Shabibah Binti Shaufit Affandi (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to explore and describe the strategies for developing Islamic educators to enhance their professional competence in response to global educational challenges and student needs. Theoretical framework: The theoretical framework is grounded in the importance of integrating pedagogical, technological, and managerial competencies to build educators’ capabilities, aligning with contemporary educational theories and Sustainable Development Goals (SDGs), particularly SDG 4 on quality education. Literature review: A review of the literature highlights persistent challenges in the consistent implementation of educator development programs and the gap between existing strategies and the holistic competencies required today. Methods: Using a descriptive qualitative research design, this study was conducted at SMP Islam Bani Hasyim Singosari Malang. Informants included the principal, three vice principals, the chairman of the national exam committee, and teachers of Indonesian, English, Arabic, and religious studies. Results: Findings reveal three core strategies in educator development: First, the Education Strategy, which includes free lectures aimed at broadening educators’ strategic and adaptive thinking; Second, the Educator Training Strategy, which is implemented in three levels to accommodate new educators, enhance existing educators’ skills, and prepare educators for leadership roles; Third, the Strategy of Cultivating and Realizing a Sense of Responsibility, focusing on practical and ethical approaches to professional development. Implications: The implications of this research suggest that a comprehensive, tiered, and responsibility-focused approach can effectively improve educator competence, curriculum relevance, and the quality of learning, thereby supporting the achievement of SDGs. Novelty: The novelty of this study lies in its integrated framework that combines education, training, and ethical responsibility cultivation tailored to Islamic educational institutions, offering a sustainable model for educator development in the era of globalization.